Upaya Peningkatan Kinerja Penyuluh Pertanian di Kawasan Hortikultura Kabupaten Wonosobo - Hadiyati, Isna Sulistami; Subagyo, Yusuf; Sukarso, Sukarso; Sari, Lilik Kartika; Makhasin, Luthfi (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study assesses horticulture farmers' perceptions of extension workers' performance and formulates improvement strategies via SWOT analysis. Conducted in three major horticultural hubs—Garung, Kertek, and Kalikajar subdistricts—82 organized farmer group members participated. Purposive sampling targeted high-production areas with active farmer institutions. Data came from Likert-scale questionnaires evaluating three aspects: preparation, implementation, and evaluation/reporting of extension activities. SWOT analysis identified internal (IFAS) and external (EFAS) factors. Findings reveal positive perceptions across all aspects: 93.90% rated preparation good (index 70.96%); 82.93% rated implementation good (69.30%); and 98.78% rated evaluation/reporting good (70.96%). Chi-Square tests confirmed no significant influence from respondent traits (age, gender, education, farming experience) on perceptions. IFAS-EFAS scores showed a strength-weakness differential of 1.008 and opportunity-threat differential of 1.060, placing strategies in Quadrant I (Aggressive/SO). Recommendations emphasize leveraging strengths for opportunities: bolstering technical competencies, optimizing IT use, developing flagship programs, and strengthening ties with local governments and stakeholders.